The QoL of College Students and Its Impact on Stress Level: A Cross-Sectional Study - Karimah, Rinda Nurul; Destarianto, Prawidya; Perwiraningrum, Dhyani Ayu; Ardianto, Efri Tri (International Journal of Health and Information System, 2025)
The peak of vulnerability to behavioral and mental disorders occurs during college, making this a crucial time for development. College students have a worse quality of life (QoL) in terms of mental health compared to the general population. There is a need for information regarding QoL related to stress in students, as studies discussing QoL and stress in college students are still lacking. This study aims to analyze the relationship between QoL and stress levels in college students. A cross-sectional survey design was used in this study, involving 249 college students at higher education institutions in East Java, Indonesia. The data samples were collected based on demographic characteristics, using the QoL scale from WHOQOL-BREF and the Depression, Anxiety, and Stress Scale-21 to assess the correlation between QoL and stress levels among college students. The results showed that the stress levels of college students were classified as normal (54.6%), mild (17.3%), moderate (17.3%), severe (8.4%), and extremely severe (2.4%). A significant negative correlation was observed between all domains of QoL and stress: Physical (-0.630), Psychological (-0.658), Social Relationship (-0.564), and Environment (-0.584). These results indicate that as QoL increases, stress scores decrease. Attention should be paid to providing appropriate interventions related to college students' quality of life. Further research is needed to gather detailed information on existing QoL domains, particularly those focusing on students’ needs, current information developments, and demographic characteristics.